Effects of high-dose glucose oxidase on broiler growth performance, antioxidant function, and intestinal microbiota in broilers - Jiang, Zipeng; Huang, Zhiyi; Du, Hongfang; Li, Yangyuan; Wang, Min; Chen, Dandie; Lu, Jingyi; Liu, Ge; Mei, Liang; Li, Yuqi; Liang, Weifan; Yang, Bo; et al. (Frontiers in Microbiology, 2024)
Glucose oxidase (GOD) has been explored as a potential additive to improve intestinal health and growth performance in the poultry industry. However, there is limited information about the ultra-high doses of GOD in practical production. This study aimed to investigate the effects of high dietary doses of GOD on the growth performance, antioxidant capacity, intestinal microbiota of broilers. 400 healthy, 1day-old, slow-growing broiler chickens were randomly assigned to four treatment groups. The Control group was fed a standard basal diet, and broilers in groups G1, G2, and G3 received the basal diet supplemented with 4 U/g, 20 U/g, and 100 U/g of VTR GOD, respectively. The results showed that 100 U/g GOD significantly increased the final weight and ADFI (P < 0.05). The GSH-Px activity dramatically increased (P < 0.05) in the G3 group. Intestinal morphology analysis revealed that the gut structure and barrier remained normal in GOD groups. Microbiota analysis revealed Firmicutes, and Verrucomicrobiota increased significantly (P < 0.05) in the GOD groups at the phylum level. Meanwhile, GOD treatments increased the abundance of Faecalibacterium, Mucispirllum, and CHKCI001 at the genus level. Metabolic function predictions suggested that high-dose GOD treatments enriched the carbohydrate metabolism (especially starch and sucrose metabolism). Correlation analysis indicated that Faecalibacterium and CHCKI001 are two bacteria influenced by GOD supplementation, which were associated with enhanced growth performance and improved gut health. In conclusion, supplementation of high-dose GOD, which did not exhibit any adverse effects, played a significant positive and beneficial role in